Decomposition of Signals and Information Theory - Plastino, Ángel Luis (1992)
We discuss a method that is able to determine, with the help of the Maximum Entropy Principle, the detailed nature of a complex signal that can be conceived as a linear superposition of independent, elementary signals. The physical relevance of this decomposition is discussed.